(untitled) (Fiep Bulletin - online, 2014)
The goal of this work is to build and validate a tool to study the environmental impact caused by the sportsman, that practices mountaineering with his own opinion describing and developing a tool (questionnaire) capable of analyzing the conduct and behavior of the mountaineer, get quantitative and qualitative data of the mountaineer, his place of activities and the possible impacts related to his behavior when practicing the sport. This tool was built, after analyzing the whole environmental problem, seeking the necessary data in order to understand and analyze this phenomena in our society, giving sources to study the sport within the environment, its variables, impact possibilities, prevention tools and protection of the ecosystem, knowing the positive and negative points of the mountaineering practice in the “Parque Nacional da Serra dos Órgãos”. Based on norms of consciousness conduct in Natural Environments, this tool intends to be more than a simple assessment questionnaire but a tool to help elaborating public politics towards sports practicing in natural environments, helping to reach the sustainability in mountaineering.